Pengembangan modul berbasis inquiry social complexity untuk meningkatkan critical and creative thinking skill - Ulwiyah, Ripa; Kariadinata, Rahayu; Maryono, Iyon (Papanda Journal of Mathematics and Science Research, 2025)
The low level of critical and creative thinking skills among students is a major challenge in mathematics learning, especially in SPLDV material that requires a deep understanding of concepts. To overcome this problem, an ISC-based module was developed, designed to improve students' critical and creative thinking skills. This study aims to: (1) develop an ISC-based module to improve students' CCT; (2) determine the validity and feasibility of the developed module; and (3) measure the effectiveness of the module's use in improving students' CCT. This study uses a research and development (R&D) method with the ADDIE model (analysis, design, develop, implement, and evaluate). The participants in this study were 40 students, consisting of 10 students in Grade VIII and 10 students in Grade IX, who were divided into a limited trial group (Grade IX) and a broader trial group (Grade VIII). The instruments used included an expert validation sheet, a student response questionnaire, and a CCT test. The results of the expert validation showed that the module was very feasible for use as teaching material. The limited trial and broader trial showed a significant increase in students' critical and creative thinking skills after using the module. Continuous evaluation through revision of the substance of the material, improvement of the design, and technical refinement of the presentation of the material also improved the quality of the module. Thus, the ISC-based module proved to be valid, feasible, and effective in improving students' CCT in SPLDV learning, as well as contributing significantly to efforts to improve the quality of mathematics learning oriented towards higher-order thinking skills.